Final consultancy report 2013: dessimination of information on two innovation technology projects implemented in the Toledo district and the formation of a national functional network in Belize - Pérez, Leonardo (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
The consultancy service officially started on the 29th of January 2013, where by a field visit to the village of Jalacte was done with the purpose of up-dating myself of the situation of the second phase of Red-sicta project which had recently ended and to familiarized with the farmers that worked in the second phase of the Red-sicta project. The objective of this consultancy was to assist in the coordination and in the implementation of the innovation technology projects and to oversee the execution of each specific project granted to different Non Governmental Organizations in Belize (Ya`axche Conservation Trust and Sustainable Harvest International) and through the projects creating a network that will actively participate in the solution of problems in corn and beans value chain.